Household savings decision and income uncertainty - Martin Beznoska; Richard Ochmann (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
This paper empirically investigates the effects of changes in the interest rate as well as transitory income uncertainty on households' consumption-savings decision. Applying a structural demand model to German survey data, we estimate the uncompensated interest rate elasticity for savings, in line with the literature, to around zero. Accordingly, any policy-induced variation of net returns to savings is expected to have no significant effects on the level of savings. Moreover, we find significant effects of precautionary savings on the consumption-savings decision. As a result of a doubling of transitory income uncertainty, an average household increases savings by 4:4%. These effects vary by household composition and social status.
Keywords: D12; D91; E21; 330; Consumption-savings decision; interest rate elasticity of savings; income uncertainty; Sparen; Zeitpräferenz; Einkommen; Risiko; Zins; Elastizität; Schätzung; Deutschland